89 The dialatation of main pulmonary arterial measured by chest multislice computed temography predict poor long-term outcome in connective tissue disease associated pulmonary arterial hypertension. (April 2019) - Li, Xiaodi; Zhang, Chunfang; Sun, Xiaoxuan; Yang, Xiaoman; Wang, Qiang; Zhu, Yinsu; Zhang, Miaojia
Abstract : Background: Pulmonary arterial dilatation is a common manifestation of chest multislice computed temography (MSCT) in patients with pulmonary arterial hypertension (PAH). The exact clinical significance of these phenomena has not been clarified in connective tissue disease (CTD) associated PAH. We want to observe whether the dilatation of pulmonary aterial was associated with poor outcome in patients with CTD-PAH. Methods: We retrospectively investigated 140 CTD-PAH patients diagnosed by echocardiography during 2010 and 2018 at the first affiliated hospital of Nanjing Medical University. Digital scout chest MSCT information was obtained. Main pulmonary arterial (MPA), right pulmonary arterial (RPA) branch, left pulmonary arterial (lPA) branch, ascending aorta (AAO) and descending aorta (DAO) diameters were measured by professional radiologist. The ratio of MPA/AAO, MPA/DAO were also caiculated. Results: During the observational period of 3.44±0.23 years, 2 patients were died of serious infection, 1 patients was died of renal failuer and 33 patients were died of heart faliure. The time dependent receiver operating characteristic (ROC) curve suggested that MPA, PRA and LPA diameter may have the 10 year prognositic value in CTD-PAH patients, the corresponding cut-off values were MPA>37.70 mm, RPA >20.46 mm and LPA >20.20 mm. Kaplan-Meier analysis showed significant difference in the long-term prognosis between patients with MPA diameter <37.70 mm and MPA diameter 37.70 mm (Long-rank test p=0.00012) and between patients with LPA diameter <20.20 mm and LPA diameter 20.20 mm (Long-rank test p=0.0091). The multivariate analyses suggested that MPA 37.70 mm was the independent risk factor of poor outcome of CTD-PAH patients (HR: 0.28; 95% CI: 0.14–0.58 p=0.01). Conclusions: Main pulmonary arterial dilatation measured by MSCT was associated with the poor prognosis in patients with CTD-PAH. Funding Source(s): None